Protohistoric cultural interactions in Atlantic Europe: a general perspective from Brittany to Galicia (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2023)
This article provides a synthetic overview of the late prehistory within the Bay of Biscay. The data are considered from the angle of the evolution of cultural interactions, in the light of recent works. The period considered extends from the Bell Beaker period to the end of the Iron Age. It seems to be characterized by alternating phases of dense interactions, which are associated with the appearance of markers of socio-political hierarchization (Early Bronze Age, Late Bronze Age, end of the Early Iron Age, end of the Second Iron Age), and phases of diminishing interactions, which are associated with the apparent disappearance or flattening of hierarchies (Middle Bronze Age, beginning of the First Iron Age, beginning of the Second Iron Age). The cultural phenomena highlighted shed light on the evolution of Palaeohispanic languages and cultures.
Keywords: Late prehistory Archaeology; Cultural interactions; Networks; Socio-political hierarchization; Cultural evolution